Actual status of therapeutic vaccination in non-small cell lung cancer - Szyszka-Barth, Katarzyna; Ramlau, Katarzyna; Goździk-Spychalska, Joanna; Spychalski, Łukasz; Bryl, Maciej; Gołda-Gocka, Iwona; Kopczyńska, Anna; Barinow-Wojewódzki, Aleksander; Ramlau, Rodryg (Contemporary Oncology/Współczesna Onkologia, 2014)
Lung cancer is the leading cause of cancer-related death worldwide. Although treatment methods such as surgery, radiotherapy and/or chemotherapy have improved, prognosis remains unsatisfactory, and developing new therapeutic strategies is still an urgent matter. Immunotherapy is a novel therapeutic approach wherein activated immune cells can specifically kill tumour cells. Several lung cancer vaccines have demonstrated prolonged survival time in phase II and III trials, and several clinical trials are under investigation. However, many clinical trials involving cancer vaccination with defined tumour antigens have shown this method to work only in a small number of patients. Cancer immunotherapy is not completely effective in eradicating tumour cells because they evade host immune control.